2023
DOI: 10.1007/s00402-023-04839-5
|View full text |Cite
|
Sign up to set email alerts
|

Osteoid osteoma in the bones of the hand: a systematic literature review

Abstract: Introduction Osteoid osteoma (OO) is a common benign bone tumor. OO is observed most frequently in the long bones, especially in the tibia and femur. When occurring in the bones of the hand, OO can be a diagnostic and therapeutic challenge. The aim of this study was to provide a systematic review of occurrence, symptoms, diagnosis and treatment options regarding OO in hand bones. Materials and methods We performed a systematic review of the literature. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…MRI of the whole compartment with adjacent joints should be carried out and is currently regarded as the best modality for local staging for tumours of the extremities. Additional CT is not mandatory but may help to evaluate bone stability and may increase sensitivity in rare tumour entities [19]. Noteworthy, a recent study focused on the quality of primary radiology MRI reports and revealed frequent deviations from the European Society of Musculoskeletal Radiology (ESSR) guidelines resulting in 25% mismatch with the histopathological diagnosis and 32% misinterpretation of the masses as benign [34].…”
Section: Soft Tissue Sarcomamentioning
confidence: 99%
“…MRI of the whole compartment with adjacent joints should be carried out and is currently regarded as the best modality for local staging for tumours of the extremities. Additional CT is not mandatory but may help to evaluate bone stability and may increase sensitivity in rare tumour entities [19]. Noteworthy, a recent study focused on the quality of primary radiology MRI reports and revealed frequent deviations from the European Society of Musculoskeletal Radiology (ESSR) guidelines resulting in 25% mismatch with the histopathological diagnosis and 32% misinterpretation of the masses as benign [34].…”
Section: Soft Tissue Sarcomamentioning
confidence: 99%
“…Alternative treatments of CT-guided percutaneous ablation of the nidus using radiofrequency (RF), laser photocoagulation (LPC), and thermocoagulation (TCG) are described. In the latter, the main complications described are local recurrence, mainly in TCG, and osteonecrosis in RF 27 .…”
Section: Benign Bone Tumorsmentioning
confidence: 99%
“…The occurrence in the carpal bones is lower, with the scaphoid being the most affected (7.7%). The most frequently observed location is within the cortical bone (intracortical), followed by cancellous bone, subperiosteal, and juxta-articular regions 27 .…”
Section: Benign Bone Tumorsmentioning
confidence: 99%
See 1 more Smart Citation